Technology-based accounting education: evidence on acceptance and usage - Abdul Wahab, Roslan; Mat Dangi, Mohamad Ridhuan; Abdul Latif, Nurul Ezhawati; Mad, Salina; Mohd. Noor, Rohana (American Scientific Publishers, 2017)
Technology-based accounting education is a step in the right direction to meet the industry demand for higher quality and IT savvy professional accountants as it is an essential component in today’s student-centered learning approach era. However, the elements that contribute to the enhancement of vital IT skills among the accounting students in a student-centered learning environment are still vague and need to be further discussed. This study measures the accounting students’ acceptance of technology-based teaching approach based on their past IT experience, actual usage of IT in education as well as computer skills. The questionnaires were randomly distributed to the accounting students in a selected Malaysian public university. This study found a significant positive relationship between the past IT experiences and the acceptance of technologybased education as well as the IT skills of the students; and between the usages of a computer laboratory with the IT skills of the students. The limitations of this study and suggestion for future research are also presented.